Differential regulation of collagenase gene expression by retinoic acid receptors--alpha, beta and gamma. - Pan, L (1992)
The mechanisms involved in retinoic acid (RA)-mediated regulation of the collagenase gene in a rabbit synovial fibroblast cell line (HIG82) were investigated. When HIG82 cells are cotransfected with expression vectors containing cDNAs for retinoic acid receptor (RAR) alpha 1, beta 2, or gamma 1 and collagenase promoter-driven CAT reporter constructs, only RAR-gamma 1 represses basal CAT expression upon RA treatment, while RAR-alpha 1, beta 2, and gamma 1 all suppress phorbol-induced CAT expression. Thus, transcriptional regulation of collagenase by RA is mediated by RARs in an RAR-type specific manner. Using mutational and deletional analysis, we find that interaction between elements within 182 bp collagenase promoter plays an important role in this process. In addition, cotreatment with RA results in a decrease of phorbol-induced mRNA levels of fos and jun, and binding of nuclear proteins to an AP-1 oligonucleotide. Furthermore, RA-induced nuclear protein(s) specifically bind to a 22 bp sequence (-182 to -161) of the collagenase promoter. We propose that RA-mediated regulation of the collagenase gene depends on the availability and interaction of specific RARs with multiple DNA elements within the promoter and with transcription factors, including AP-1 related proteins.